CFD study of mass transfer in spacer filled membrane module - Hussain, Sharmina (GANIT: Journal of Bangladesh Mathematical Society, 2012)
The present paper is devoted to investigate the mass transfer in two dimensional spacer filled channels. Three different configurations of the cylindrical spacers are considered with different channel Reynolds number and mesh length. Different size and shape of formation of recirculation region, upstream and downstream of the spacers are closely observed. This recirculation regions have an important role in enhancing the mass transfer in the reattachment region. CFD simulations show that the submerged spacers have the highest efficiency with highest wall shear stress and mass transfer enhancement whilst the cavity spacer have the least performance. DOI: http://dx.doi.org/10.3329/ganit.v31i0.10306 GANIT J. Bangladesh Math. Soc. (ISSN 1606-3694) 31 (2011) 33-41